FAKTOR DAN JENIS BAHASA YANG TERDAPAT DALAM PENCAMPURAN KOD DALAM MASYARAKAT LUNDAYEH/LUNBAWANG - Patricia Rinai, Sakai Connie (Universiti Malaysia Sarawak (UNIMAS), 2020)
Mixing codes in languages when communicating is not uncommon in Malaysia because it has a multi-racial society. For the Lundayeh/Lunbawang community, the cause of this mixing of codes is often associated with the aspects of education, employment and marriage. However, no comprehensive study has been conducted to examine the actual factors of this code mixing occurring in the Lundayeh/Lunbawang community. In this study, we had looked at the use of Lundayeh/Lunbawang language in everyday speech. From his analysis, we had identify the dominant factor of code mixing for the Lundayeh/Lunbawang community in Lawas and the dominant language in speech among these community. The methodology of this study uses an explanary study design. Data were collected from Lundayeh/Lunbawang respondents of different background in terms of age, education, occupation, status and so on. The main instruments in this study are online questionnaire in the form of a "Likert" scale and spontaneous audio recording followed by interviews. The result of this study showed that the dominant factor in code mixing for the Lundayeh/Lunbawang community is the message comprehension. This is because there are a few terms which do not have any translation in Lundayeh/Lunbawang. In addition, the dominant language used by the Lundayeh/Lunbawang community in Lawas is their own mother tongue which is the Lundayeh/Lunbawang language itself. This study showed that the code mixing occurring in this community has led to a positive development from the aspect of communication because it allows the community to communicate effectively.